Regulating difference: religious diversity and nationhood in the secular west - Burchardt, Marian (Rutgers University Press, 2020)
Religious Diversity, Secularism and Nationhood -- Theorizing Religious Diversity and Secularism -- Contesting Religious Diversity and Secularism -- Spatializing Religious Diversity: Urban Administration, Infrastructure and Emplacement -- The Limits of Religious Diversity: Regulating Full-Face Coverings -- Making Claims to Religion as Culture: The Rise of Heritage Religion